PAI Learning and Strengthening Students' Belief Education at SMA Swasta BUDISATRYA Medan - Siagian, Fitri Alkomariah; Nahar, Syamsu (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This study aims to determine the approach used in Islamic Religious Education learning to improve students' creed education, efforts made by Islamic Religious Education teachers to improve students' creed education, and changes in students' personalities after Islamic Religious Education teachers' efforts in strengthening students' creed education at SMA Swasta BUDISATRYA Medan. This research method uses descriptive qualitative methodology and a kind of field research, with data collection through interviews, observation and documentation. The data analysis techniques used are, data reduction, data presentation, data verification, and conclusion making are the data analysis procedures used. The results of this study are: 1) The approach used in PAI learning in strengthening students' faith education such as: Practicing approach, habituation approach, emotional approach, rational approach, functional approach, and exemplary approach. 2) PAI teachers' efforts in strengthening students' faith education are learning and habituation. Learning activities in the form of PAI teaching and learning activities, which include all PAI material in one book. While habituation activities, namely, religious activities or worship practices. 3) Changes in students' personalities after the PAI teacher's efforts in strengthening students' creed education, for example, some students have experienced changes, such as having a sense of tawadhu to both parents and teachers, and so on, but there are still some students who do not follow the activities carried out by PAI teachers to form better students.